A hybrid switched inductor with flexible high voltage gain boost converter for DC micro‐grid application. Issue 9 (27th May 2021) - Al‐Hitmi, Mohammed; Maroti, Pandav Kiran; Iqbal, Atif
Abstract: A hybrid switched inductor with flexible high voltage gain boost converter for 400 V DC microgrid application is presented in the paper. The three operating modes of the converter are controlled using three switches by two‐duty ratios. The proposed converter provides flexibility in the selection of the duty cycle to achieve desired output voltage. Moreover, with two duty ratio, high gain with a wide duty range is accomplished in the proposed converter while an individual switch does not need to operate at a very large duty ratio. The power circuit analysis, operating principles, steady‐state voltage gain analysis during continuous conduction mode (CCM) and discontinuous continuous mode (DCM), boundary condition, efficiency analysis, comparison, and circuit parameter design of the proposed are presented. A closed‐loop controller design and small‐signal modeling are discussed. The dynamic behavior of the proposed converter is validated with a change in duty ratio, input voltage, and load power. A laboratory prototype converter is designed and developed to verify the model, and feasibility of different operation modes. The prototype is tested for a power range of 100 W–500 W for different duty cycles.